Penerapan Statistik Manajemen dalam Pengambilan Keputusan di Bidang Administrasi Pendidikan - Prihaten Maskhuliah; Sastya Nawangsari; Nirmaya Rumakat; Mohamad Salis Garamatan; Ardiyanto N. Tupong (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Decision-makers in educational administration face increasingly complex challenges along with the need for accountability, honesty, and quality education services. Based on the book "Statistics of Management and Administration" by Dr. Cucu Supriyatna (2020), the purpose of this article is to examine the application of management statistics as a decision-making tool in educational administration. A literature review using a descriptive-analytical approach was used to collect data from 2020 to 2025. The results indicate that management statistics are crucial in four main aspects: (1) data-driven strategic planning of educational institutions; (2) descriptive analysis for organizing resources; (3) statistical control for monitoring quality; and (4) inferential-based performance evaluation. This study concludes that incorporating management statistics into the educational administration cycle can improve decision-making fairness, reduce personal bias, and enhance the accountability of educational institutions. This study concludes that the integration of management statistics into the educational administration cycle can improve the quality of decision-making, strengthen institutional accountability, reduce reliance on individual subjectivity, and create a more transparent and data-driven culture of educational management.